Early growth response 1 reduction in peripheral blood involving condylar subchondral bone loss. (19th August 2019) - Zhang, Hong‐Yun; Liu, Qian; Yang, Hong‐Xu; Shi, Li‐Qiang; Wang, Pei; Xie, Mian‐Jiao; Liu, Jin‐Qiang; Xu, Xiao‐Jie; Liu, Xiao‐Dong; Yu, Shi‐Bin; Jiao, Kai; Zhang, Mian; et al.
Abstract: Objectives: To detect whether early growth response 1 (EGR1) in peripheral blood leucocytes (PBLs) indicates temporomandibular joint (TMJ) osteoarthritis (OA) lesions. Materials and Methods: Egr1 mRNA expression levels in PBLs were detected in eight malocclusion patients without temporomandibular disorder (TMD) signs and 16 malocclusion patients with clinical TMD signs with (eight) or without (eight) imaging signs of TMJ OA. Twelve 6‐week‐old rats were randomized to a control group and a unilateral anterior crossbite (UAC) group and were sampled at 4 weeks. The Egr1 mRNA expression levels in PBLs and protein expression levels in different orofacial tissues were measured. Results: Patients with TMD signs with/without TMJ OA diagnosis showed lower Egr1 mRNA expression levels in PBLs than patients without TMD signs. The lower Egr1 mRNA expression was also found in the PBLs of UAC rats, which were induced to exhibit early histo‐morphological signs of TMJ OA lesions. In subchondral bone of UAC rats, EGR1 protein expression was decreased, co‐localization of EGR1 with osterix or dentin matrix protein‐1 was identified, and the number of EGR1 and osterix double‐positive cells was reduced (all p  < .05). Conclusion: Egr1 reduction in PBLs potentially indicates subchondral bone OA lesions at an early stage.